כיצד מכפילים ומפשטים את frac {x ^ {2} - 3x - 10} {x ^ {2} - 4x - 12} cdot frac {6 x} {x ^ {2} - 25}?

כיצד מכפילים ומפשטים את frac {x ^ {2} - 3x - 10} {x ^ {2} - 4x - 12} cdot frac {6 x} {x ^ {2} - 25}?
Anonim

תשובה:

# -1 / (x + 5) # #

הסבר:

קודם כל אנחנו גורמים לכל דבר:

# (x + 2) (x-2) (x-5)) / (x + 2) (x-6)) (x-6) 2) (x-5) (x-5) (x-5) (x-5) (x + 2) (x-6) (x-5) (x + 5)

(x-5) (x-5) (x-5) (x-5) (x-6)) (x-5) (x-5) 5)) = (6-x) / (x-6) (x + 5)) #

# (6-x) = - (x-6) #

# (X-6) (x-6) (x-6) (x + 5) = = (x-6) / (x-6)